Gaze Direction and Estimation Model Based on Iris Center Coordinates - Sharma, Anjana; Abrol, Pawanesh (International Journal of Computer Sciences and Engineering, 2025)
An appearance cum feature based iris center gaze detection model viz. Iris Center Based Gaze Estimation (ICGE) is proposed to detect the direction of gaze quadrants to overcome certain limitations like dependency on light sources, multiple glint formation, no formation of glint etc, observed in glint based gaze quadrant detection models. The model works on the adaptive thresholding technique for the detection of the iris center coordinates using more than two hundred images from an indigenous database of different subjects on a five quadrants map screen. The model works with the Circular Hough Transform (CHT) for localising circles in the eye images and then center coordinates on the iris edge for further detection of gaze quadrants. Gaze directions of five different positions of iris are estimated on a mapped screen within the eye region. The model generates almost ninety percent accurate results for correct iris and gaze quadrant detection. The distinguishing features of the low cost, non intrusive proposed model include non IR and affordable ubiquitous hardware designing, large subject-camera distance and screen dimensions, no glint dependency etc. The proposed model also shows significantly better results in the lower periphery corners of the quadrant map. The proposed model may be more suitable for interactive applications for healthy users who cannot use head and hands freely while doing other tasks or disabled users who have no movement in their hands and head etc.